PEMANFAATAN METODE MARKER BASED TRACKING PADA TEKNOLOGI AUGMENTED REALITY (AR) UNTUK RANCANG BANGUN APLIKASI TUNTUNAN SHOLAT PADA PLATFORM ANDROID - Fitriastuti, Fatsyahrina; Irsyadi, Hijrul (Universitas Janabadra, 2021)
Prayer is a compulsory worship for every Muslim. Therefore, from the earliest possible time the children should begin to be taught to pray so that later when they reach the compulsory age for praying, the children are ready. Various methods can be applied by parents and teachers to teach how to perform prayers with the correct prayer movements and readings. The rapid development of information and communication technology, both in terms of hardware and software, can be used as a tool to create learning media for prayer guidance. Among them is the android based augmented reality (AR) technology. AR or known as